Multifunctional sound-absorbing and heat-insulating foamed ceramic prepared by synergistically using multi-source solid waste
Through the collaborative preparation technology of multi-source solid waste, high-efficiency sound-absorbing, lightweight, and heat-insulated foam ceramics are prepared using materials such as construction waste, which solves the shortcomings of existing materials in noise control and environmental protection, and achieves efficient utilization of resources and environmental sustainability.
Patent Information
- Application Number
- CN202510062110.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-18
AI Technical Summary
Existing building materials have shortcomings in noise control and environmental protection, and ceramic production relies on expensive natural mineral resources, resulting in resource waste and environmental pollution.
Through the coordinated preparation of multi-source solid waste, materials such as construction waste, coal gangue, fly ash, waste glass slag, combined with additives such as silicon carbide, aluminum fluoride, polyvinyl alcohol and molybdenum oxide are prepared to produce multifunctional foam ceramics with good sound absorption performance, lightweight and heat insulation.
It realizes building materials with excellent sound absorption performance, low cost and environmentally friendly, solves the problem of consumption of construction waste and mineral resources, and reduces noise pollution and environmental pressure.
Smart Images

Figure CN119841620A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a novel building sound-absorbing and heat-insulating material, in particular to a multifunctional sound-absorbing and heat-insulating foam ceramic prepared by synergistically using multi-source solid wastes. Background Art
[0002] my country's urbanization process is advancing year by year, and the renovation of roads, houses, bridges and other facilities is becoming more and more frequent. Noise pollution has long become one of the environmental problems that affect people's health. Sound-absorbing porous materials play a vital role in controlling noise pollution. Sound-absorbing porous materials are generally divided into organic porous materials, inorganic porous materials and metal porous materials. Organic porous materials have a lower cost, but poor flame retardancy and stability. Metal porous materials are expensive and susceptible to corrosion. Compared with other materials, inorganic materials have a lower cost. Among them, ceramic materials are widely used in construction, aerospace, biomechanics and other fields due to their high temperature resistance and corrosion resistance. They show excellent stability and have received widespread attention and application in recent years. At the same time, a large number of new construction, demolition, and reconstruction projects in the process of urbanization have led to a large increase in construction waste. According to statistics, about 1.5 billion tons of construction waste is generated nationwide each year, accounting for 30% to 40% of the total urban waste. It has become the second largest solid waste after domestic waste. A large amount of construction waste cannot be effectively disposed of. Except for backfill utilization in engineering construction, most of the construction waste will be directly transported to the suburbs for storage. This will not only damage the surrounding ecological environment, but also seriously affect the quality of life of surrounding residents.
[0003] my country consumes about 200 million tons of natural mineral resources in the ceramic production process every year. Natural mineral raw materials are limited in nature and expensive. Construction waste is mainly composed of inorganic materials such as bricks, concrete fragments, and tiles. The main components of these inorganic materials are SiO 2 、Al 2 O 3 , CaO, FeO, etc., whose components basically meet the requirements for preparing porous ceramics. Using construction waste combined with coal gangue, fly ash and waste glass slag to prepare sound-absorbing and heat-insulating foam ceramics can solve the problems of pollution caused by the storage of large amounts of solid waste such as construction waste and environmental noise pollution, as well as the problems of high prices for ceramic production and consumption of mineral resources. Therefore, exploring the method of preparing sound-absorbing and heat-insulating ceramics from construction waste can bring huge social and economic benefits. Summary of the invention
[0004] Based on the problems existing in the above-mentioned prior art, the present invention provides a multifunctional sound-absorbing and thermal-insulating foam ceramic prepared by the coordinated utilization of multi-source solid waste, aiming to achieve the coordinated utilization of multi-source solid waste and produce a multifunctional building sound-absorbing and thermal-insulating material with good sound absorption performance, light weight and heat insulation.
[0005] In order to achieve the purpose, the present invention adopts the following technical scheme:
[0006] A multifunctional sound-absorbing and heat-insulating foam ceramic prepared by the coordinated use of multi-source solid wastes, wherein the raw materials are composed of: 40 parts of construction waste; 15 parts of coal gangue; 20 parts of waste glass slag; 25 parts of fly ash; 0.7 parts of silicon carbide, 0.8 parts of aluminum fluoride, 0.3 parts of polyvinyl alcohol, and 0.8 parts of molybdenum oxide.
[0007] The preparation method of the multifunctional sound-absorbing and heat-insulating foam ceramic of the present invention is: after pre-treating the raw materials, mixing, tableting, drying, sintering and cooling according to the proportion, so as to obtain the sound-absorbing and heat-insulating foam ceramic. Specifically, the steps include:
[0008] Step 1, after drying the construction waste and coal gangue at 80°C for 4 hours, crush them and pass through a 100-mesh standard sieve; dry the fly ash at 80°C for 2 hours for later use; crush the glass slag, pass through an 80-mesh standard sieve, and dry it at 80°C for 2 hours for later use;
[0009] Step 2: Mix
[0010] The pre-treated construction waste, coal gangue, fly ash and glass slag, as well as silicon carbide, aluminum fluoride, polyvinyl alcohol and molybdenum oxide as additives are mixed according to a proportion, put into a sample preparation pulverizer and pulverize for 1.5 minutes to obtain a mixed raw material;
[0011] Step 3: Tablet pressing
[0012] After adding 14 parts of water to the mixed raw materials and mixing them evenly, an electric hydraulic press is used with molds of different sizes to press and prepare samples to obtain ceramic wet blanks;
[0013] Step 4: Drying
[0014] The ceramic wet blank obtained in step 3 is placed in a drying oven and dried at 105° C. to fully remove the moisture in the wet blank to obtain a ceramic dry blank;
[0015] Step 5: Sintering
[0016] The ceramic dry blank obtained in step 4 was heated to 1000°C at 5°C / min, kept at this temperature for 30 minutes, and then continued to be heated to 1205°C at 3°C / min, and sintered at this temperature for 50 minutes;
[0017] Step 6: Cooling
[0018] The sintered ceramic is cooled to room temperature to obtain the target product.
[0019] Furthermore, the mold size in step 3 can be set as needed. The present invention selects Φ30 mm and Φ100 mm for subsequent testing.
[0020] The present invention uses construction waste as the main raw material to replace kaolin for preparing traditional foam ceramics, adds coal-based solid waste gangue and fly ash to prepare ceramic basic raw material components, and adds glass slag to adjust the molten state at high temperature, which is conducive to the growth and uniform distribution of pores. Adding aluminum fluoride and molybdenum oxide as catalysts and promoters of mullite, respectively, is conducive to the formation of mullite at high temperature and thus improves the mechanical strength of the sample. Adding SiC as the main foaming agent can increase the porosity of the sample. Adding polyvinyl alcohol as a binder makes the internal bonding of the ceramic body tight, improves the mechanical strength of the ceramic body, and avoids breakage or crushing during transportation. The main reactions occurring at high temperature are as follows:
[0021] ①Silicon carbide reacts with oxygen to generate gas:
[0022] SiC (s) +2O 2(g) =SiO 2(s) +CO 2(g)
[0023] 2SiC (s) +3O 2(g) =2SiO 2(s) +2CO (g)
[0024] SiC (s) +O 2(g) =SiO 2(s) +C (s)
[0025] 2SiC (s) +3O 2(g) =2SiO (s) +2CO 2(g)
[0026] SiC (s) +O 2(g) =SiO (s) +CO (g)
[0027] ②High temperature reaction of ferrous oxide
[0028] 6FeO (s) +O 2(g) →2Fe 3 O 4(s)
[0029] 4FeO (s) +O 2(g) →2Fe 2 O 3(s)
[0030] ②High temperature reaction of aluminum fluoride
[0031] 6A3 +3O 2 →6AlOF+12F
[0032] Al 2 O 3 +2F→2AlOF+0.5O 2
[0033] 2SiO 2 +8F→2SiF 4 +2O 2
[0034] 6AlOF+2SiF 4 +3.5O 2 →3Al 2 O 3 ·2SiO 2 +14F
[0035] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0036] 1. The production process of the present invention is simple and environmentally friendly, and the raw materials used are low-cost and abundant in source, and can be scaled up for production.
[0037] 2. The present invention utilizes construction waste as the main raw material and combines it with low-cost raw materials such as fly ash to solve the problem of large-scale storage of construction waste, coal gangue, fly ash, etc. occupying land resources and reducing their pollution to the environment. It also reduces the problem of construction noise pollution and promotes the simple high-value utilization of solid waste.
[0038] 3. The apparent density of the foam ceramic obtained by the present invention reaches 569.11 kg / m 3 The compressive strength reaches 2.2MPa. The small pore size of the ceramic is concentrated at about 0.3mm, the large pore size is concentrated at about 1.05mm, the sound absorption coefficient reaches 0.43, which is greater than the sound absorption coefficient requirement of 0.2 for general sound-absorbing materials. The thermal conductivity is 0.073W / (m·K), which is a high-efficiency sound-absorbing and thermal insulation material.
[0039] 4. The present invention uses high temperature sintering to make the ceramic produce liquid phase at high temperature, and the alkali metal ions Na in the raw materials + , K + The viscosity of the liquid phase will be reduced, so that SiC is further oxidized and more pores are generated. The true pores of the foam ceramic obtained by the present invention are as high as 83%, and the open porosity is about 52.7%. Some small open pores are embedded in the closed pores, and the air in the closed pores has a lower thermal conductivity. The open pores can allow sound waves to pass through the interior of the foam ceramic, so that the sound wave propagation path is continuously extended, and the sound absorption capacity of the foam ceramic is improved.
[0040] 5. The foam ceramic obtained by the present invention has an average sound absorption coefficient of 0.43 at a frequency of 200Hz-6300Hz. It can absorb noise in the environment when applied to buildings. Using this sound-absorbing ceramic to treat the walls and ceilings of buildings can reduce the spread of sound, control the noise within a certain range, and thus protect the hearing health of residents. In addition, due to the low density of the foam ceramic, it can effectively reduce the noise in the building while reducing the composite of the non-bearing structure, thereby improving the overall lightweight level.
[0041] 6. The thermal conductivity of the foam ceramic of the present invention is as low as 0.073W / (m·K). The low thermal conductivity can effectively reduce the heat transfer between indoor and outdoor and reduce the heat loss. Compared with other ceramic thermal insulation materials currently available, its thermal insulation performance is very excellent and it is a high-efficiency thermal insulation material.
[0042] 7. The foam ceramics obtained by the present invention can also be used in the field of waste gas and wastewater purification. Foam ceramics have a three-dimensional spatial grid structure and high porosity. There are a large number of small and interconnected pores inside. The large specific surface area can be used as a catalyst carrier to increase the reaction contact area of the catalyst. When waste gas and wastewater pass through the foam ceramics, the particles will be intercepted by the pores and contact the catalyst. At the same time, foam ceramics have the characteristics of high temperature resistance and corrosion resistance, and can maintain stable physical and chemical properties in the waste gas and wastewater environment, thereby increasing its service life.
[0043] 8. Through the method of the present invention, construction waste, coal gangue, fly ash, waste glass slag, etc. are transformed into raw materials, which not only solves the harm of their large-scale storage to the social environment, but also develops new sound-absorbing and heat-insulating ceramic products, and reuses them as building materials in construction, realizing the perfect unity of economic benefits, environmental benefits and social benefits, and effectively reconciling the contradictions between economic benefits and social benefits and environmental effects.
[0044] In summary: 100% of the raw materials used in the present invention come from the construction industry or industrial solid waste, which fully utilizes waste residues and waste materials, saves resources, protects arable land, and reduces environmental pollution. It is a successful practice to improve building materials and has significant social and economic benefits. Due to the high porosity, good sound absorption performance, high-quality heat insulation and light weight, the product obtained by the present invention can not only be used as a material for non-load-bearing insulation and sound-absorbing wall panels inside and outside buildings, but also can be used as a catalyst carrier in the field of waste gas and wastewater purification, and degrade harmful substances generated in automobile exhaust, chemical industry exhaust, sewage treatment and other processes. The ceramics obtained by the present invention can be widely used in insulation and sound-absorbing building walls, exhaust gas purification, catalyst carriers and other aspects, and the application prospects are very broad. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 This is a process diagram for preparing the foam ceramic of the present invention;
[0046] Figure 2 is the X-ray diffraction spectrum of the foam ceramic obtained in Example 1;
[0047] Figure 3 TG-DTG-DSC curve of the foam ceramic obtained in Example 1;
[0048] Figure 4 The microscopic morphology of the foam ceramic obtained in Example 1
[0049] Figure 5 This is the sound absorption frequency distribution diagram of the foam ceramic obtained in Example 1;
[0050] Figure 6 This is the radioactivity spectrum of the foam ceramic obtained in Example 1. DETAILED DESCRIPTION
[0051] In order to make the above-mentioned purposes, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the accompanying drawings. The following content is only an example and explanation of the concept of the present invention. The technicians in the relevant technical field make various modifications or supplements to the specific implementation cases described or replace them with similar methods. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
[0052] The construction waste and glass slag raw materials used in the embodiment of the present invention are solid waste stored in a building materials enterprise. The chemical composition and main parameters of the solid waste are shown in Table 1.
[0053] Table 1 Chemical composition of construction waste and glass slag
[0054]
[0055] The gangue used in the embodiment of the present invention is provided by a certain environmental protection building materials company, and its chemical composition is shown in Table 2. Gangue is a solid waste discharged during coal mining and coal washing in the coal industry, and its output accounts for about 10% to 25% of the total raw coal output. Even though the comprehensive utilization rate of gangue in my country has increased in recent years, most of the gangue is still improperly disposed, occupying a large amount of land, and will release toxic substances for a long time, posing a threat to the ecological environment and the health of the surrounding people.
[0056] Table 2 Chemical composition of coal gangue
[0057]
[0058] The fly ash used in the embodiment of the present invention is the fine ash captured after the combustion of coal in a thermal power plant. As an industrial by-product of coal-fired power plants, the production volume of fly ash will remain high for a long time. Its resource utilization is relatively wide, and most of it is low-value utilization in the field of construction engineering. There are few high-value utilization paths involving fields such as high-microcrystalline glass and ceramic materials. The chemical composition of the fly ash used in the present invention is similar to that of construction waste. It is used as a composite raw material for the production of foam ceramics, which realizes the high-value utilization of solid waste, saves resources and protects the environment. Its chemical composition is shown in Table 3.
[0059] Table 3 Chemical composition of fly ash
[0060]
[0061] Example 1
[0062] This embodiment prepares foam ceramics according to the following steps:
[0063] Step 1: Dry the construction waste and coal gangue at 80°C for 4 hours, crush them and pass through a 100-mesh standard sieve; dry the fly ash at 80°C for 2 hours for later use; crush the glass slag, pass through an 80-mesh standard sieve, and dry it at 80°C for 2 hours for later use.
[0064] Step 2: Mix
[0065] 40 parts of pretreated construction waste, 15 parts of coal gangue, 25 parts of fly ash, 20 parts of glass slag, 0.7 parts of silicon carbide, 0.8 parts of aluminum fluoride, 0.3 parts of polyvinyl alcohol, and 0.8 parts of molybdenum oxide were mixed, put into a sample preparation grinder and crushed for 1.5 minutes to obtain a mixed raw material.
[0066] Step 3: Tablet pressing
[0067] After adding 14 parts of water to the mixed raw materials and mixing them evenly, an electric hydraulic press is used with molds of different sizes (Φ30 mm and Φ100 mm) to press and prepare samples to obtain ceramic wet blanks.
[0068] Step 4: Drying
[0069] The ceramic wet blank obtained in step 3 is placed in a drying oven and dried at 105° C. to fully remove the moisture in the wet blank to obtain a ceramic dry blank.
[0070] Step 5: Sintering
[0071] The ceramic dry blank obtained in step 4 was heated to 1000°C at a rate of 5°C / min, kept at that temperature for 30 minutes, and then continued to be heated to 1205°C at a rate of 3°C / min, and sintered at that temperature for 50 minutes.
[0072] Step 6: Cooling
[0073] The sintered ceramic is cooled to room temperature to obtain the target product.
[0074] The properties of the foam ceramic obtained in this example were tested as follows:
[0075] 1. Physical performance analysis
[0076] Foam ceramics were prepared according to the above process, and foam ceramics of two diameters were polished to appropriate sizes for subsequent related performance tests.
[0077] The diameter of the small sample after grinding is about 29 mm, which is used to test its true porosity, compressive strength, apparent density, thermal conductivity and sound absorption coefficient at 2000-6300 Hz; the diameter of the large sample after grinding is about 99 mm, which is used to test the sound absorption coefficient at 200-2000 Hz. Table 4 shows the different physical properties of the foam ceramics obtained in Example 1.
[0078] Table 4 Physical properties of foam ceramics obtained in Example 1
[0079] Sound absorption coefficient (200-2000Hz) 0.08-0.78 Sound absorption coefficient (2000-6300Hz) 0.47-0.96 Average sound absorption coefficient (200-6300Hz) 0.43 Thermal conductivity / [W / (m·K)] 0.073W / (m·K) <![CDATA[Apparent density / (kg / m 3 )]]> <![CDATA[569.11kg / m 3 ]]> Compressive strength / (MPa) 2.2MPa Aperture range / mm Small hole 0.3mm, large hole 1.05mm Open porosity / (%) 52.7% True porosity / (%) 83%
[0080] (1) Thermal conductivity
[0081] Thermal conductivity is one of the important physical properties of building materials, which has a great influence on the energy consumption, indoor and outdoor environment and heat and humidity process of buildings. It refers to the heat transferred through 1 square meter in a period of time under relatively stable heat transfer conditions, when the temperature difference between the two sides of the material with a thickness of 1 meter is 1°C. Thermal conductivity is affected by its own material composition, true porosity, temperature and humidity of the environment in which the material is located, and the direction of heat flow. As we all know, air has relatively low thermal conductivity, and air trapped in pores can act as an excellent thermal insulator, so generally speaking, materials with high true porosity have lower thermal conductivity.
[0082] The thermal conductivity of the foam ceramics in this embodiment is measured using a DRX-JG laser thermal conductivity measuring instrument. The sample is irradiated with a laser, and the temperature rise on the back of the sample is measured with an infrared detector to calculate the thermal diffusion coefficient of the sample and then the thermal conductivity. According to GB50176-2016 "Civil Building Thermal Design Code", the thermal conductivity of thermal insulation materials is <0.25K / (m·K). It has been measured that the thermal conductivity of the foam ceramics in this embodiment is 0.073W / (m·K). Due to its non-combustibility, according to GB8624-97, this product belongs to Class A WW thermal insulation building materials, and has significant thermal insulation performance.
[0083] (2) Compressive strength
[0084] The compressive strength of the foam ceramic obtained in this embodiment reaches 2.2 MPa, which is higher than the compressive strength requirement of 0.6 MPa for L-shaped exterior wall external insulation foam ceramics specified in GB / T 33500-2017, and meets the thermal conductivity requirement of less than 0.100 W / (m·K), and is a lightweight, thermal insulation foam ceramic.
[0085] (3) Porosity
[0086] Porosity refers to the ratio of the volume of pores in a material to the total volume of the material. It can be divided into open porosity and closed porosity according to the type of pores. The sum of the two is the true porosity. The Archimedean method is used to measure the open and closed porosity of foam ceramics. The true porosity of the foam ceramics in this embodiment is 83%, and the open porosity is about 52.7%. The open pores can ensure that sound waves can effectively enter the interior of the ceramic, causing the air molecules in the pores to vibrate, and friction occurs between the air molecules and the pore walls, converting the sound energy into heat energy and consuming it. The air sealed in the closed pores can act as an excellent thermal insulator, which is equivalent to forming an isolation layer inside the material, reducing the direct contact between the solid skeletons inside the material, thereby greatly reducing the path of heat conduction through the solid and improving the thermal insulation performance of the material.
[0087] 2. Microscopic performance analysis
[0088] The foam ceramics and mixed raw materials obtained in this example were taken for X-ray diffraction analysis and standing wave tube sound absorption performance analysis, and the ceramic cross section was used for scanning electron microscope microscopic morphology analysis. The mixed raw materials were subjected to thermogravimetric analysis.
[0089] (1) X-ray diffraction analysis
[0090] The X-ray diffraction pattern of the foam ceramic obtained in this example is as follows: Figure 2 As shown (the diffraction scanning interval is 5-80°, and the scanning speed is 5° / min), it can be seen that the main crystal phase of the foam ceramic is Quartz, with a small amount of Kyanite and Mullite. The appearance of quartz and mullite crystal phases makes the ceramic have a certain compressive strength.
[0091] (2) Thermal analysis
[0092] Take the foam ceramic sample obtained in this example, heat it at 10°C / min in the range of 25-1100°C, conduct microscopic thermal mechanism analysis, and draw a TG-DTG-DSC curve. Figure 3As shown. It can be seen that the total weight loss of the sample is about 3.94%. The weight loss of the raw material from room temperature to 370°C is about 1.18%, and the DSC curve shows an obvious endothermic peak at 200°C. This stage is mainly the removal of free water and bound water in the raw material. From 370 to 800°C, the TG curve drops significantly, and the weight loss is the largest, about 2.22%. This part may be accompanied by the combustion of combustibles and organic matter in the raw material. The thermogravimetric curve at 800 to 1100°C tends to be flat, the combustion of organic matter and combustibles ends, and the mass loss is 0.54%. SiC undergoes oxidation reaction in the air after 800°C, and the oxidation rate increases rapidly when the temperature is greater than 1100°C.
[0093] (3) Microscopic morphology
[0094] Figure 4 This is an electron microscope image of the cross section of the foam ceramic obtained in this example. It can be observed that there are a large number of pores inside the ceramic, all of which have similar structures, and the adjacent pore walls present a "Y"-shaped structure with an angle of about 120°. The pores can be divided into two categories according to their different locations: one is the pores generated by the reaction of SiC to CO 2 Gases such as CO and CO are retained in small pores in the ceramic matrix. These small pores are embedded in the thicker pore walls of the sample. The gas in the pores can effectively improve the thermal insulation performance as a good thermal insulator. The other type is large pores generated by the gradual merger of small pores. The large pores and small pores form a resonant cavity. The resonant cavity is composed of pores, pores and short and narrow connecting windows. When the sound wave diffuses into the window, it will produce sound wave resonance. The resonance will push the air in the pores to move up and down, causing repeated friction with the pore wall to dissipate the energy of the incident sound wave.
[0095] (4) Sound absorption performance test
[0096] The standing wave ratio method is the most commonly used method for measuring sound absorption coefficient in the laboratory. Samples are prepared according to the requirements of GB / T18696.1-2004 "Measurement of sound absorption coefficient and acoustic impedance in acoustic impedance tubes Part 1: Standing wave ratio method" and relevant performance tests are performed. The results of 200-6300Hz are as follows: Figure 5 As shown, the sound absorption coefficients of foam ceramics at 1250Hz and 3150Hz are 0.78 and 0.96 respectively, and the average sound absorption coefficient at all frequencies is 0.43, which is a good sound absorbing material.
[0097] (5) Radioactivity detection
[0098] The foam ceramic obtained in this example is crushed and ground to a particle size of less than 0.16 mm, and 500.0 g is weighed and placed in a sample box. When the natural radioactive decay chain in the test sample is basically balanced, the specific activities of radium-226, thorium-232, and potassium-40 are measured using a low-background multi-channel gamma spectrometer under the same measurement conditions as the standard sample, thereby obtaining the foam ceramic internal illumination index I Ra The external illumination index is 0.14. r is 0.33, and its radioactivity spectrum is as follows Figure 6 According to the national standard GB6566-2010, it meets the radiation ratio requirements of building main body materials with a hollow ratio greater than 25%, and is a Class A high-quality environmentally friendly building material.
[0099] Comparative Example 1
[0100] The difference between the sound-absorbing and heat-insulating foam ceramics of this comparative example and Example 1 is that silicon carbide is not added. The specific raw material components are:
[0101] 40 parts of construction waste, 15 parts of coal gangue, 25 parts of fly ash, 20 parts of glass slag, 0.8 parts of aluminum fluoride, 0.3 parts of polyvinyl alcohol, and 0.8 parts of molybdenum oxide.
[0102] Comparative Example 2
[0103] The difference between the sound-absorbing and heat-insulating foam ceramics of this comparative example and Example 1 is that the amount of silicon carbide added is 0.2 parts, and the specific raw material components are:
[0104] 40 parts of construction waste, 15 parts of coal gangue, 25 parts of fly ash, 0.2 parts of silicon carbide, 20 parts of glass slag, 0.8 parts of aluminum fluoride, 0.3 parts of polyvinyl alcohol, and 0.8 parts of molybdenum oxide.
[0105] Comparative Example 3
[0106] The difference between the sound-absorbing and heat-insulating foam ceramic of this comparative example and Example 1 is that the amount of silicon carbide added is 1.5 parts, and the specific raw material components are:
[0107] 40 parts of construction waste, 15 parts of coal gangue, 25 parts of fly ash, 1.5 parts of silicon carbide, 20 parts of glass slag, 0.8 parts of aluminum fluoride, 0.3 parts of polyvinyl alcohol, and 0.8 parts of molybdenum oxide
[0108] Comparative Example 4
[0109] The difference between the sound-absorbing and heat-insulating foam ceramic of this comparative example and Example 1 is that the sintering temperature of step 5 is 1195° C. The specific sintering conditions are as follows:
[0110] The temperature was raised to 1000°C at 5°C / min, kept at this temperature for 30 minutes, and then the temperature was raised to 1195°C at 3°C / min, and kept at this temperature for 50 minutes.
[0111] Comparative Example 5
[0112] The difference between the sound-absorbing and heat-insulating foam ceramic of this comparative example and Example 1 is that the sintering temperature of step 5 is 1215° C. The specific sintering conditions are as follows:
[0113] The temperature was raised to 1000°C at 5°C / min, kept at this temperature for 30 minutes, and then the temperature was raised to 1215°C at 3°C / min, and kept at this temperature for 50 minutes.
[0114] The sound absorption coefficient, thermal conductivity and porosity of each embodiment and comparative example were tested using the AWA6290Z standing wave tube test system, DRX-JG thermal conductivity meter and Archimedes boiling method, so as to comprehensively evaluate the sound absorption and heat preservation ability of the samples. The test results are shown in Table 5.
[0115] Table 5 Physical properties of foam ceramics obtained in Example 1
[0116]
[0117] According to the data in Table 5, the multifunctional sound-absorbing and heat-insulating foam ceramic prepared by the synergistic use of multi-source solid waste disclosed in the present invention has a good sound absorption coefficient and extremely low thermal conductivity, and therefore has good noise reduction and heat preservation functions, which makes it have good application prospects in sound-absorbing and heat-insulating building walls.
[0118] The above are merely exemplary embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A multifunctional sound-absorbing and heat-insulating foam ceramic prepared by synergistic use of multi-source solid waste, characterized in that: The composition of the raw materials in parts by weight is: 40 parts of construction waste; 15 parts of coal gangue; 20 parts of waste glass slag; 25 parts of fly ash; 0.7 parts of silicon carbide, 0.8 parts of aluminum fluoride, 0.3 parts of polyvinyl alcohol, and 0.8 parts of molybdenum oxide.
2. A method for preparing the multifunctional sound-absorbing and heat-insulating foam ceramic according to claim 1, characterized in that: The raw materials are pretreated, mixed, tableted, dried, sintered and cooled according to a ratio, so as to obtain the multifunctional sound-absorbing and heat-insulating foam ceramic.
3. The preparation method according to claim 2, characterized in that: The specific steps include: Step 1, after drying the construction waste and coal gangue at 80°C for 4 hours, crush them and pass through a 100-mesh standard sieve; dry the fly ash at 80°C for 2 hours for later use; crush the glass slag, pass through an 80-mesh standard sieve, and dry it at 80°C for 2 hours for later use; Step 2: Mix The pre-treated construction waste, coal gangue, fly ash and glass slag, as well as silicon carbide, aluminum fluoride, polyvinyl alcohol and molybdenum oxide are mixed according to a proportion, put into a sample preparation pulverizer and pulverize for 1.5 minutes to obtain a mixed raw material; Step 3: Tablet pressing After adding an appropriate amount of water to the mixed raw materials and mixing them evenly, an electric hydraulic press is used to press the samples to obtain a ceramic wet blank; Step 4: Drying The ceramic wet blank obtained in step 3 is placed in a drying oven and dried at 105° C. to fully remove the moisture in the wet blank to obtain a ceramic dry blank; Step 5: Sintering The ceramic dry blank obtained in step 4 was heated to 1000°C at 5°C / min, kept at this temperature for 30 minutes, and then continued to be heated to 1205°C at 3°C / min, and sintered at this temperature for 50 minutes; Step 6: Cooling The sintered ceramic is cooled to room temperature to obtain the target product.
4. The preparation method according to claim 3, characterized in that: In step 3, the amount of water added is 14 parts.